STUDI KORELASIONAL ANTARA SIKAP TERHADAP ENTREPRENEUR DENGAN ETIKA ORGANISASI PIMPINAN PTAIS DI KOPERTAIS I - Suharyat, Yayat (Edukasi, 2009)
The objective of the research is to study the relationship between attitude towards entrepreneur and organization ethics. The study was conducted at Kopertais I Jakarta in the year of 2003 with n=60 selected randomly. The finding of the research reveals that there is a positive correlation between attitude towards entrepreneur and organization ethics. Based on the results of the study, organization ethics could be enhanced by improving, attitude towards entrepreneur, charismatic leadership, and emotional intelligence.